The first translations of Machiavelli's Prince : from the sixteenth to the first half of the nineteenth century - De Pol, Roberto (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2010)
This book is the first complete study of the translations of Machiavelli's Prince made in Europe and the Mediterranean countries during the period from the sixteenth to the first half of the nineteenth century: the first, unpublished French transla.